Physical activity and emotional intelligence in Spanish undergraduates: A comparative study by autonomous region - Sanz-Martín, Daniel; Caracuel-Cáliz, Rafael Francisco; Alonso-Vargas, José Manuel; Melguizo-Ibáñez, Eduardo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
A cross-sectional study was conducted with the following aims: 1) to assess the levels of physical activity and emotional intelligence of Spanish undergraduates of Teaching Degrees according to the autonomous region and 2) to analyze the relationship between physical activity and emotional intelligence of Spanish undergraduates based on their place of residence. The participants were undergraduates of the Teaching Degrees residing in Andalusia, Castile and Leon, Madrid and Melilla, who completed an online questionnaire covering sociodemographic information, physical activity (IPAQ-SF) and emotional intelligence (TMMS-24). The results showed that the university students performed 422.15±461.74 minutes/week of moderate-vigorous physical activity and showed high levels of emotional intelligence (attention: 30.28±6.11; clarity: 28.05±6.31; emotional repair: 28.57±6.09). It was concluded that the majority of university students meet the recommendations for physical activity. Moreover, the vigorous physical activity of Andalusian university students is positively related to attention, clarity and emotional repair.